A Study of Cover Materials Which Influence Rn222 Exhalation Indoors - Raptis, C.; Savidou, A.; Kritidis, P. (HNPS Advances in Nuclear Physics, 2019)
The wall covers can decrease or increase the radon exhalation; this depends on whether the material acts mostly as a sealer against radon exhalation or as a source of radon. This work is a study of different kind of wall covers which influence radon exhalation from surfaces of building materials. The experimental data are in good agreement with the evaluations according to the theory of radon diffusion through porous materials.